Interaction of dinuclear ruthenium(II) supramolecular cylinders with DNA: sequence-specific binding, unwinding, and photocleavage - Malina, Jaroslav; Hannon, Michael J; Brabec, Viktor (Chemistry, 2008)
Metallosupramolecular chemistry was used to design a new class of synthetic agents, namely, tetracationic supramolecular cylinders, that bind strongly and noncovalently in the major groove of DNA. To gain additional information on interactions of the cylinders with DNA we explored DNA unwinding and sequence-specific binding properties, as well as DNA photonuclease activity of ruthenium(II) metallosupramolecular cylinder [Ru(2)L(3)](4+), where L is a bis-pyridylimine ligand. We found that [Ru(2)L(3)](4+) unwinds negatively supercoiled plasmid DNA and exhibits binding preference to regular alternating purine-pyrimidine sequences in a similar way to the [Fe(2)L(3)](4+) analogue. Photocleavage studies showed that, unlike [Fe(2)L(3)](4+), [Ru(2)L(3)](4+) induces single-strand breaks on irradiation by visible and UVA light and cleaves DNA mainly at guanine residues contained preferentially in regularly alternating purine-pyrimidine nucleotides. As [Ru(2)L(3)](4+) binds and cleaves DNA in a sequence-dependent manner, it may provide a useful tool for basic and applied biology, such as for controlled manipulation of the genome.
Keywords: ethidium; fotochemie; molekulární sekvence - údaje; Ligands; Models, Molecular; DNA; Photochemistry; sloučeniny ruthenia; Ethidium; Ruthenium Compounds; sekvence nukleotidů; ligandy; Base Sequence; Plasmids; plazmidy; molekulární modely; Molecular Sequence Data